KUHP dan KUHAP Perdebatan Hukum, Kebebasan Sipil, dan Peran Mahkamah Konstitusi dalam Peninjauan Judicial Review - Siti Nur Ambarini; Masharin Masharin; Iyus YL Tobing; Arif Hardiyanto; Adzan Dylan Caesarrio; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article examines the ongoing legal debates surrounding Indonesia's Criminal Code (KUHP) and Criminal Procedure Code (KUHAP), focusing on their implications for civil liberties and the pivotal role of the Constitutional Court in judicial review processes. The recent revisions to the KUHP have sparked significant public discourse, raising concerns about potential infringements on fundamental rights, particularly freedom of expression and assembly. Simultaneously, the KUHAP, as the procedural framework, governs the implementation of criminal law and its impact on the rights of the accused. This research aims to analyze the contested provisions within both codes, explore the arguments put forth by various stakeholders, and critically assess the Constitutional Court's jurisprudence in adjudicating challenges to these laws. Employing a normative legal research methodology, the study will delve into statutory interpretations, legal theories, and comparative legal perspectives to provide a comprehensive understanding of the legal complexities. The findings will highlight the delicate balance between maintaining public order, upholding human rights, and ensuring the rule of law in a democratic society. Ultimately, this article seeks to contribute to the ongoing scholarly discourse on legal reform in Indonesia and offer insights into the future direction of its criminal justice system.